Professional position of cadets of educational organizations of the Ministry of Internal Affairs of Russia: concept, meaning, peculiarities - Korotkova A. S. (Modern educational process: psychological and pedagogical support, educational strategies, 2024)
Modern educational standards are regularly undergoing a number of transformations and modifications in order to improve the educational system of our state and improve the quality of trained personnel in higher educational organizations of different levels. Training of future specialists for internal affairs bodies is carried out in special, established on the basis of educational organizations of the Ministry of Internal Affairs of Russia, structural subdivisions of professional training. Professional position of cadets, as a fundamental element that ensures their full-fledged solvency in the implementation and maintenance of their official status and functional purpose, is one of the main tasks in the framework of improving the level of the educational system of the Ministry of Internal Affairs of Russia.
Keywords: образовательный процесс; профессиональная позиция; educational process; образовательное пространство; educational space; курсанты; cadets; образовательные организации МВД России; professional position; educational organizations of the Ministry of Internal Affairs of Russia